BLOOD-BRAIN BARRIER OF CAPILLARIES OF THE BRAINSTEM OF DOMESTIC CHICKEN - Vladimir Ponamarev; Alexey Prusakov (Archives of Veterinary Medicine)
The aim of the study was to establish the structural organization of the blood-brain barrier of the brainstem capillaries of domestic chicken. The material used for the study was fragments of the brainstem tissue of the White Loman cross chicken. Their fixation and further processing to produce ultrathin sections were carried out in accordance with generally accepted methods. The obtained sections were examined using an electron microscope Jem-1011. The manuscript was written using the terminology of the International Histological Nomenclature. It was established that the brainstem blood-brain barrier of domestic chicken is formed by four structural elements: endothelial cells, basal membrane, pericytes, and processes of glial cells in astrocytes. The endotheliocytes that form the lumen of the capillaries are in contact using tight junctions, preventing the possibility of large molecular compounds to penetrate the blood-brain barrier. If there are pericytes accompanying the capillary, they are surrounded by cleavages of their basal membrane. The latter form a single layer along the capillaries, surrounding their wall from the outside. These structures ensure the selective transport of substances from the bloodstream to the nervous tissue.